Returns to higher education subjects and tiers in China - Evidence from the China Family Panel Studies - Lili Kang; Fei Peng; Yu Zhu (Global Labor Organization (GLO), 2018)
Using the recent China Family Panel Studies, we are able to identify the subjects studied of both college (2-3 years) graduates and university (4-5 years) graduates. For the latter group, we can further distinguish universities by the tier of selectivity (i.e. Key and Ordinary Universities). We take advantage of the rich information on the respondent's school cohort and hukou status at age 12 and the mother's age and education to estimate the simultaneous choice of subject and tier of prestige of higher education institutions (HEI) faced by university applicants. Using the doubly robust Inverse Probability Weighted Regression Adjustment (IPWRA) method to account for selection (on observables) into subjects and tiers, our treatment effect estimates suggest that OLS substantially underestimate the effect of attending more prestigious universities, for graduates of both genders in Law, Economics and Management (LEM). We also show that the recent massive expansion of the higher education sector have reduced returns to HE for all graduates, except for those studying LEM or Other non-STEM subjects at the most prestigious universities. Our results are robust to treating subjects as predetermined for the selection into HEIs by tiers of prestige.
Keywords: I23; I26; 330; Returns to university tier and subjects; China; Inverse Probability Weighted Regression Adjustment; Higher Education expansion